Mining revenue, fiscal space and social policies: The case of Zambia - Rafaël Aguirre Unceta (International Policy Centre for Inclusive Growth (IPC-IG), 2021)
Mining resources have played an important role in the economy of Zambia. The country faces serious development challenges. This Working Paper investigates to which extent the mining of natural resources has facilitated public action regarding these challenges or whether, on the contrary, mining has had a neutral or even counterproductive impact.
Keywords: 330; Zambia; natural resources; taxation; public finances; development policies